The Differences of The Students Mathematics Learning Outcomes Under The Implementation of The Long Multiplication and Chinese Multiplication - Siti Subuh Hemi; Sukidin Sukidin; Tri Dyah Prastiti (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
The multiplication operations of whole numbers to solve the Mathemamtical problems were long multiplication and Chinese multiplication. Long multiplication of whole numbers was implemented by SD Negeri Darungan 01 Jember, while Chinese multiplication was considered as one of the most remarkable ways to calculate multiplication with more than two numbers. The students found it easier in counting than memorizing through the use of crossed lines. This design of this research was quantitative research method. The quantitative approach and quasi-experimental research were taken into this. As many as 64 respondents covering 32 students of class VIA and the other 32 of class VIB were selected by using the independent sample t-test technique. The data collection method used was observation, interview and tests. The learning outcomes through long multiplication showed that the mean score of pretest was 49.50, below the minimum completeness criteria; whilst the post-test obtained was 75.63. Learning outcomes achieved in pretest by using long multiplication revealed that the mean score was below the KKM, which was 45.00. After administering posttest, the mean score was 63.38. According to hypothesis verification through t-test polled variance on the students' posttest scores, the t-count was 3.434 in which it was lower than the t-table of 2.2971. The students who solved the problems by using Chinese multiplication learning got the higher mean scores of posttest which was 73.16 than the ones who obtained the mean score of 62.66 by using long multiplication. Thus, there was found a significant difference in the scores of students’ learning outcomes through long multiplication and Chinese multiplication techniques.